2016
DOI: 10.1111/jfd.12567
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feed supplementation with kynurenic acid on the morphology of the liver, kidney and gills in rainbow trout (Oncorhynchus mykiss Walbaum, 1792), healthy and experimentally infected with Yersinia ruckeri

Abstract: Kynurenic acid (KYNA) is an endogenous substance produced on the kynurenine pathway which is primarily known for its neuroactive properties. Recently, it has been proven that KYNA is a selective ligand for G protein-coupled receptor (GPR 35), presented on immunocompetent cells such as T lymphocytes. This opens up new possibilities of its application as an immunostimulating substance in aquaculture. Thus far, no histopathological investigations in fish have been completed to evaluate influence of KYNA supplemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
(63 reference statements)
0
8
0
Order By: Relevance
“…The intermediates of the kynurenine pathway, due to their toxic potential, may cause tissue damage and, as a consequence, generate higher stress, which can in turn interfere with the immune response to minimize tissue damage. It was recently observed that feed supplementation with kynurenic acid (KYNA) in rainbow trout had a toxic/stress-inducing effect, and this deleterious effect was related to the dose of KYNA ( 65 ). This pathological status was manifested during a subsequent infection with Yersinia ruckeri , with a higher mortality rate in animals that were administered a higher concentration of KYNA ( 65 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intermediates of the kynurenine pathway, due to their toxic potential, may cause tissue damage and, as a consequence, generate higher stress, which can in turn interfere with the immune response to minimize tissue damage. It was recently observed that feed supplementation with kynurenic acid (KYNA) in rainbow trout had a toxic/stress-inducing effect, and this deleterious effect was related to the dose of KYNA ( 65 ). This pathological status was manifested during a subsequent infection with Yersinia ruckeri , with a higher mortality rate in animals that were administered a higher concentration of KYNA ( 65 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was recently observed that feed supplementation with kynurenic acid (KYNA) in rainbow trout had a toxic/stress-inducing effect, and this deleterious effect was related to the dose of KYNA ( 65 ). This pathological status was manifested during a subsequent infection with Yersinia ruckeri , with a higher mortality rate in animals that were administered a higher concentration of KYNA ( 65 ). On the other hand, kynurenic acid is an endogenous agonist of gpr35 (which was the second most upregulated gene in β-glucan-stimulated zebrafish in the absence of infection), and its activation increases FAO and induces an anti-inflammatory state ( 66 , 67 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the microbial-mediated KYNA catabolism, known so far from Pseudomonas and Aerococcus ( 60 , 61 ), might be relevant. Interestingly, feed supplementation with very high amounts of KYNA might have a toxic/stress-inducing effect in rainbow trout ( 161 ). Hence, further studies are necessary to evaluate if a supplementation of KYNA is beneficial or detrimental to human health.…”
Section: Kyna Microbiota and Gut Homeostasismentioning
confidence: 99%
“…KYNA has a key role in numerous biological species and their environment. The natural abundance of this biomolecule is essential in plants [19], in animal feed [20], in amphibians as pheromones [21] and moreover in fish as lymphocyte-activators [22] with potential aggravating properties [23].…”
Section: Resultsmentioning
confidence: 99%